International Saudi Arabia Students’ Level of Preparedness: Identifying Factors and Maximizing Study Abroad Experience Using a Mixed-Methods Approach - Brutt-Griffler, Janina; Nurunnabi, Mohammad; Kim, Sumi (Journal of International Students, 2020)
Given that students’ level of preparedness for study abroad is malleable, this study aimed to assess Saudi students’ level of preparedness academically and socioculturally to enhance their overseas experiences and success in higher education. Using a mixed methods research design consisting of survey data, semistructured interviews, and case studies with undergraduate and graduate students in a predeparture Saudi context and those enrolled in U.S. programs, the study provides empirical data to understand students’ intent to study abroad, local institutions’ contributions to preparation, and challenges encountered. Findings across datasets corroborated that Saudi students are highly motivated, while articulating the need for substantive supports toward a better understanding of U.S. higher education, academic expectations, and sociocultural practices. Participants articulated the need for advanced English skills, especially academic literacies (academic writing and reading strategies) to cope with demanding workloads in graduate programs. The study discusses curricular implications for higher education in binational contexts.